2006
DOI: 10.1002/ijc.21755
|View full text |Cite
|
Sign up to set email alerts
|

Asthma history, occupational exposure to pesticides and the risk of non‐Hodgkin's lymphoma

Abstract: We previously reported that, although asthma did not increase the risk of non-Hodgkin's lymphoma (NHL), the risk from pesticide exposures was higher among asthmatics than that among nonasthmatics. To further evaluate this finding, we analyzed data from a population-based case-control study of NHL conducted in Iowa, Detroit, Los Angeles and Seattle. Cases (n 5 668) diagnosed with NHL from 1998 to 2000 and controls (n 5 543) randomly selected from the same geographical areas as that of the cases were included in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
14
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(17 citation statements)
references
References 15 publications
3
14
0
Order By: Relevance
“…Furthermore, this study17 found an identical risk of NHL from DDT exposure for non‐asthmatic farmers (OR = 1.2, 95% CI: 0.9–1.5) and asthmatic farmers (OR = 1.2, 95% CI: 0.6–2.4), whereas our analysis showed a higher risk of NHL among asthmatics who used DDT. Another study from Iowa, Los Angeles County, Seattle, and the Detroit Metropolitan Area18 found that the odds of NHL associated with probable occupational exposure to pesticides was higher among asthmatics (OR = 1.7, 95% CI: 0.3–9.1) compared to non‐asthmatics (OR = 0.9, 95% CI: 0.6–1.5), which is what we observed for overall pesticide use. Vajdic et al ,19 in an evaluation of the effects of asthma, hay fever, eczema, and food allergy on the association between pesticide exposure and risk of NHL, observed that the odds of NHL with substantial pesticide exposure and any history of asthma was 3.07 (95% CI: 0.55–17.10); while for no asthma history, the risk was 4.23 (95% CI: 1.76–10.16).…”
Section: Discussionsupporting
confidence: 77%
See 4 more Smart Citations
“…Furthermore, this study17 found an identical risk of NHL from DDT exposure for non‐asthmatic farmers (OR = 1.2, 95% CI: 0.9–1.5) and asthmatic farmers (OR = 1.2, 95% CI: 0.6–2.4), whereas our analysis showed a higher risk of NHL among asthmatics who used DDT. Another study from Iowa, Los Angeles County, Seattle, and the Detroit Metropolitan Area18 found that the odds of NHL associated with probable occupational exposure to pesticides was higher among asthmatics (OR = 1.7, 95% CI: 0.3–9.1) compared to non‐asthmatics (OR = 0.9, 95% CI: 0.6–1.5), which is what we observed for overall pesticide use. Vajdic et al ,19 in an evaluation of the effects of asthma, hay fever, eczema, and food allergy on the association between pesticide exposure and risk of NHL, observed that the odds of NHL with substantial pesticide exposure and any history of asthma was 3.07 (95% CI: 0.55–17.10); while for no asthma history, the risk was 4.23 (95% CI: 1.76–10.16).…”
Section: Discussionsupporting
confidence: 77%
“…We also evaluated the effects of a group comprised of other immune conditions (hay fever, celiac disease, rheumatoid arthritis, or acne) in an exploratory fashion. These conditions were selected for analysis because they had been hypothesized to increase NHL risk,7 were available in the CCSPH, and were relevant to earlier studies that explored the potential effect modification of asthma,17–19 hay fever, eczema, and food allergy19 on pesticide exposure and NHL risk. NHL risks were estimated from these groups of immunologic conditions and self‐reported ever/never use of: ( i ) any pesticide; ( ii ) any organochlorine insecticide; ( iii ) any organophosphate insecticide; ( iv ) any phenoxy herbicide; ( v ) selected individual pesticides [1,1′‐(2,2,2‐trichloroethylidene)bis[4‐chlorobenzene]; 1,1,1‐trichloro‐2,2‐bis(4‐chlorophenyl) ethane (DDT), malathion, (4‐chloro‐2‐methylphenoxy)acetic acid (MCPA), mecoprop, and (2,4‐dichlorophenoxy)acetic acid (2,4‐D)]; and ( vi ) from the number of potentially carcinogenic pesticides reportedly used (see Appendix A for a complete list of pesticides in these six groups).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations